Implementasi Perlindungan Hukum Korban Tindak Pidana Terorisme : Upaya Pertahanan Dan Keamanan Negara - Az Zanubiya, Siti Syafa; Triadi, Irwan (CV. Era Digital Nusantara, 2024)
An important aspect related to the crime of terrorism is human rights. Terrorism is essentially the destruction of human values, national dignity, and religious norms. Therefore, it is mandatory to provide legal protection to victims of terrorism as stated in Undang Undang No. 15 Tahun 2003 because in reality, victims of crime have not received adequate protection. The problem is interesting to study, regarding the implementation of legal protection for victims of criminal acts and Orientation of Regulations that regulate the rights of victims of criminal acts of terrorism have sufficient needs to support the defense and security efforts of the state The method used is normative juridical emphasizing the study of library materials and the disclosure of the meaning of a positive legal norm. In the Indonesian context, various relative rehabilitation and reintegration programs have also established several institutional instruments and special anti-terrorism task forces. Value orientation, TNI involvement is based on the consideration that terrorism crimes that have occurred in Indonesia are serious crimes that endanger the state ideology.